IMF Survey, Volume 31, Issue 13. - International Monetary Fund. External Relations Dept. (Washington, D.C. : International Monetary Fund, 2002)
Leaders of the Group of Eight countries gathered in Kananaskis, Canada, June 26-27, for a summit that focused on terrorism, the global economy, and building a new partnership for Africa's development. It was their first meeting since the terrorist attacks of September 11. It was announced that Russia, which since 1997 has participated in summit meetings with the Group of Seven immediately following the annual G-7 summits, and which this year participated more fully as a member of the summit group, will in 2006 assume the presidency of the G-8 and host the summit. The June 2003 summit will be held in France.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet